2007
DOI: 10.1007/s10578-007-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Learning Disorder: Analysis of Family Variables

Abstract: Insecure attachment styles in parents appeared associated with maladaptive emotional-behavioral strategies in their children and may be interpreted as a risk factor for the development of the latter. More specifically, internalizing behavior in children appeared associated with dimensions pointing to dismissing attachment in fathers and to preoccupied attachment in mothers, while externalizing behavior appeared associated with dimensions indicating preoccupied attachment in both parents. Possible interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Although psychiatric diagnoses are rare, a subset of approximately 40% displayed inattention, hyperactivity, social withdrawal, and atypical behaviors that affected parents’ ability to manage the child's physical and emotional needs. The prevalence of behavioral and emotional problems detected by the CBCL is very high when compared to typically developing Italian children [Gritti et al, ] and adolescents [Frigerio et al, ], but not when compared to populations with neurodevelopmental disorders, such as intellectual [Masi et al, ] and learning [Capozzi et al, ] disabilities. In our sample, internalizing problems (anxiety/sociality) were confirmed as common, and the CBCL total score was negatively correlated with the level of global social adaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Although psychiatric diagnoses are rare, a subset of approximately 40% displayed inattention, hyperactivity, social withdrawal, and atypical behaviors that affected parents’ ability to manage the child's physical and emotional needs. The prevalence of behavioral and emotional problems detected by the CBCL is very high when compared to typically developing Italian children [Gritti et al, ] and adolescents [Frigerio et al, ], but not when compared to populations with neurodevelopmental disorders, such as intellectual [Masi et al, ] and learning [Capozzi et al, ] disabilities. In our sample, internalizing problems (anxiety/sociality) were confirmed as common, and the CBCL total score was negatively correlated with the level of global social adaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…McGillivray and Baker [30] emphasized the likelihood of the co-occurrence of ADHD and SLD since they found that the diagnosis of both disorders is significantly much higher than for ADHD alone. Capozzi et al [12] also found ADHD symptoms to be the most prevalent in children in their SLD sample and reported that the prevalence of ADHD in the population with SLD might vary from 15.0 to 25.0 % according to different studies, while Du Paul [14] pointed out that approximately 31.0-45.0 % of students with SLD have ADHD. Although significant, our prevalence of ADHD (8.2 %) in the general SLD sample was lower than these figures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that children with learning difficulties show a greater risk for psychopathology compared with typically developing children and several studies have shown that, within a given mild ID population, between 24% and 54% of subjects present with serious emotional, social and behavioural problems (Dekker & Koot et al . 2002; Capozzi et al . 2008).…”
Section: Discussionmentioning
confidence: 99%